Group of lesbian marchers - Sahl, Ted (photographer):::Creator::::::::::::
Photograph shows a group of lesbian marchers at the National March on Washington for Lesbian and Gay Rights. Marchers hold is a banner that reads, "We die united" and a second banner that reads, "We are every-where".